A comparative mechanistic study of the reversible binding of NO to a water-soluble octa-cationic FeIII porphyrin complex - Jee, Joo-Eun; Wolak, Maria; Balbinot, Domenico; Jux, Norbert; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 2006)
The water-soluble, non-μ-oxo dimer-forming porphyrin, [5,10,15,20-tetrakis-4′-t-butylphenyl-2′,6′-bis-(N-methylene- (4″-t-butylpyridinium))porphyrinato]iron(III) octabromide, (P )Fe, with eight positively charged substituents in the ortho positions of the phenyl rings, was characterized by UV-vis and H NMR spectroscopy and O NMR water-exchange studies in aqueous solution. Spectrophotometric titrations of (P)Fe indicated a pK value of 5.0 for coordinated water in (P)Fe(HO). The monohydroxo-ligated (P)Fe(OH)(HO) formed at 5 < pH < 12 has a weakly bound water molecule that undergoes an exchange reaction, k = 2.4 × 10 s, significantly faster than water exchange on (P)Fe (HO), viz. k = 5.5 × 10 s at 25°C. The porphyrin complex reacts with nitric oxide to yield the nitrosyl adduct, (P)Fe (NO)(L) (L = HO or OH). The diaqua-ligated (P)Fe(HO) binds and releases NO according to a dissociatively activated mechanism, analogous to that reported earlier for other (P)Fe(H O) complexes. Coordination of NO to (P )Fe(OH)(HO) at high pH follows an associative mode, as evidenced by negative ΔS and ΔV values measured for this reaction. The observed ca. 10-fold decrease in the NO binding rate on going from six-coordinate (P)Fe(HO) (k = 15.1 × 10 M s) to (P)Fe(OH)(HO) (k = 1.56 × 10 M s at 25°C) is ascribed to the different nature of the rate-limiting step for NO binding at low and high pH, respectively. The results are compared with data reported for other water-soluble iron(III) porphyrins with positively and negatively charged meso substituents. Influence of the porphyrin periphery on the dynamics of reversible NO binding to these (P)Fe complexes as a function of pH is discussed on the basis of available experimental data. © 2006 American Chemical Society.